Congenital extra calvarial plexiform neurofibroma in occipito-cervical region with Occipital bone defect with neurofibromatosis type 1 and segmental neurofibromatosis: Case report and review of literature - Kankane, Vivek Kumar (J Pediatr Neurosci, 2016)
Plexiform neurofibroma (PNF) of the scalp is an extremely rare lesion reported in association with neurofibromatosis (NF). Occipital location of PNF is even more infrequent; we reported one pediatric case of PNF in occipito-cervical region with multiple small occipital bone defects and associated with NF-1.